Nonlinear Relationship Between Myeloperoxidase Levels and Helicobacter pylori Infection Risk in Chinese Adults: A Population-Based Cross-Sectional Study - Zhou, Junteng; Kong, Qihang; Liu, Xiaojing; Huang, Yan (Journal of clinical medicine, 2025)
Objectives: This study investigates the nonlinear association between myeloperoxidase (MPO) levels and Helicobacter pylori (H. pylori) infection risk in Chinese adults, evaluating potential modifiers and clinical implications for infection prevention. Methods: An analysis was conducted on cross-sectional data from 15,180 adults who underwent routine health examinations between January and December 2021. H. pylori infection was diagnosed using the 14C-urea breath test with a threshold of disintegrations per minute (DPM) ≥ 100. ELISA was used to measure plasma MPO levels. Nonlinear associations were assessed through logistic regression, restricted cubic splines, threshold effect analysis, and subgroup interactions. Results: The study identified a U-shaped correlation between MPO levels and the risk of H. pylori infection. Compared to the middle tertile (T2: 20.6–31 ng/mL), participants in the lowest (T1: ≤20.6 ng/mL; OR = 1.36, 95% CI: 1.24–1.49) and highest tertiles (T3: ≥31 ng/mL; OR = 1.12, 1.02–1.22) exhibited elevated infection risk after full adjustment (p < 0.001). DPM levels were notably elevated in T1 (β = 37.1, 26.66–47.57) and T3 (β = 19.27, 8.81–29.72) relative to T2 (p < 0.0001). RCS-based threshold analysis identified a nonlinear inflection at 24.0 ng/mL of MPO, where each additional 1 ng/mL of MPO below this threshold was associated with a reduced infection risk (OR = 0.959, 95% CI: 0.947–0.971), whereas levels above increased the risk (OR = 1.004, 95% CI: 1.002–1.007). This pattern aligned with H. pylori breath test values, which mirrored the U-shaped trend across MPO tertiles. Subgroup analyses revealed uniform associations between MPO and H. pylori infection risk/DPM across various factors such as age, sex, BMI, and metabolic comorbidities, with all interaction p-values exceeding 0.05. Conclusions: MPO levels exhibit a robust U-shaped association with H. pylori infection risk, independent of anthropometric and metabolic confounders. Monitoring MPO may aid in identifying individuals at bidirectional infection risk, suggesting novel insights into the inflammation–infection interplay. The study’s cross-sectional design limits the ability to establish causal relationships, necessitating further longitudinal research to validate these findings and elucidate their clinical implications.